Faithfully seeking understanding: selected writings of Johannes Kuhn - Kuhn, Johannes von; Kaplan, Grant (Catholic University of America Press, 2009)
Introduction to selected writings / Grant Kaplan -- The false choice between faith and rational understanding -- The precedence of faith over reason -- The finality of Christian revelation -- Revelation and its salvific import -- Revelation as history -- Grace and the problem of freedom -- Neo-scholasticism and the misunderstanding of grace -- Sources of revealed truth: scripture and tradition -- Authority and interpretation -- Is history mythic? a biblical response to D.F. Strauss (co-translated with Jonathan King) -- Religion as feeling or illusion? a contrary position -- The newness of tradition -- The personhood of God -- The place of theology in a university: a response